Bleaching Susceptibility and Resistance of Octocorals and Anemones at the World’s Southern-Most Coral Reef - Steinberg, Rosemary K; Ainsworth, Tracy D; Moriarty, Tess; Bednarek, Teresa; Dafforn, Katherine A; Johnston, Emma L (Frontiers in Physiology, 2022)
Coral reefs are amongst the most biodiverse ecosystems on earth, and while stony corals create the foundational complexity of these ecosystems, octocorals and anemones contribute significantly to their biodiversity and function. Like stony corals, many octocorals contain Symbiodiniaceae endosymbionts and can bleach when temperatures exceed the species’ upper thermal limit. Here, we report octocoral bleaching susceptibility and resistance within the subtropical Lord Howe Island coral reef ecosystem during and after marine heatwaves in 2019. Octocoral and anemone surveys were conducted at multiple reef locations within the Lord Howe Island lagoon during, immediately after, and seven months after the heatwaves. One octocoral species, Cladiella sp. 1, experienced bleaching and mortality, with some bleached colonies detaching from the reef structure during the heatwave (presumed dead). Those that remained attached to the benthos survived the event and recovered endosymbionts within seven months of bleaching. Cladiella sp. 1 Symbiodiniaceae density (in cells per µg protein), chlorophyll a and c2 per µg protein, and photosynthetic efficiency were significantly lower in bleached colonies compared to unbleached colonies, while chlorophyll a and c2 per symbiont were higher. Interestingly, no other symbiotic octocoral species of the Lord Howe Island lagoonal reef bleached. Unbleached Xenia cf crassa colonies had higher Symbiodiniaceae and chlorophyll densities during the marine heatwave compared to other monitoring intervals, while Cladiella sp. 2 densities did not change substantially through time. Previous work on octocoral bleaching has focused primarily on gorgonian octocorals, while this study provides insight into bleaching variability in other octocoral groups. The study also provides further evidence that octocorals may be generally more resistant to bleaching than stony corals in many, but not all, reef ecosystems. Responses to marine heating events vary and should be assessed on a species by species basis.